IMPLEMENTASI SHARABLE CONTENT OBJECT REFERENCE MODEL DALAM LEARNING MANAGEMENT SYSTEM (Studi Kasus pada AKMI Baturaja) - , Pujianto; , Dr. Techn. Ahmad Ashari, M.Kom. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
To enhance an e-learning system become a system with e-learning SCORM (Sharable Content Object Reference Model) standard requiring the development on the content and its environment. Many e-learning systems owned by various institutions today still doesnât based on SCORM . This study aims to realize an e-learning system that has a SCORM standard, especially on its content so that later can be integrated into a variety of LMS (Learning Management Systems) or e-learning system that already supports SCORM. The method used in this study is making the content of the materials, assignments, questions and then change them into SCORM standard. The contents then uploaded into the system. SCORM-based content creation is using open source tools. Testing is done by download the contents that already in SCORMbased and integrate them into LMS. LMS used in testing is Dokeos and Moodle. Conclusion obtained from this study is that a SCORM-based content requires a wrapper which is part of the API that serves to wrap the content to be implemented in an LMS that supports SCORM. A SCORM-based content that comes with a file sharable content object that serves to handle actions that occur when content is run in the LMS. SCORM-based content packages generated in the form of zip file extension, this content can be added to the resource in other elearning systems that already have SCORM standard.